PET-CT in oesophageal cancer management: a cost effectiveness analysis (CEA) / Nor Aniza Azmi - Azmi, Nor Aniza (Institute of Graduate Studies, UiTM, 2018)
This study involved assessment of clinician's views on practicality, clinical efficacy and cost -effectiveness of PET-CT in oesophageal cancer management and decision making model-based economic evaluation to investigate the relative cost-effectiveness of PET/CT in oesophageal cancer management staging based on review of publications and retrospective data. Total of 73 clinicians included in the survey. Retrospective analysis of patient data from 2001-2008 taken from Royal Liverpool &Broadgreen University Hospital Trust (RLBUHT) medical records and North West Cancer Intelligence Services (NWCIS) database for the same period. A decision tree was developed using TREEAGE software. The relevant data on accuracy, sensitivity and specificity of each diagnostic test were linked in the model, to cost and the primary outcome measure, cost per quality-adjusted life-year (QALY). The model estimated the mean cost associated with each diagnostic procedure and assumed that patients entering the model were aged 35-75 years. The results of the cost-effectiveness analysis are presented in terms of the incremental cost-effectiveness ratios (ICERs).PET compared with conventional work-up results for ICER for the strategy estimated at £28,460 per QALY; PET/CT compared with PET for ICER was £ 32,590 per QALY; and the ICER for PET/CT combined with conventional workup versus PET/CT was £ 44,118. The package become more expensive with each additional diagnostic test added to PET and the more effective in terms of QALYs gained. The conventional work-up is the preferred options as probabilistic sensitivity analysis shows at a willingnessto- pay (WTP) threshold of £ 20,000 per QALY. Result of the current analysis suggests that the use of PET/CT in the diagnosis of oesophageal cancer is unlikely to be cost-effective given the current WTP thresholds that are accepted in the United Kingdom by decision-making bodies such as the National Institute for Health and Clinical Excellence and National Health Services. Based on the current model and given the limitations that are apparent in terms of limited availability of data, the modelling suggests that the most cost-effective diagnostic strategy are the conventional work-up given current data. Future studies need to secure robust cost data that can be verified from more than one source for the diagnostic tests involved. It is also crucial to have reliable and verifiable data on quality of life associated with this clinical condition.